Improving Seed Systems for Women and Disadvantaged Groups in Uganda - Katabalwa, Charles; Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Yila, Jummai (International Center for Tropical Agriculture, 2024)
Smallholder farmers, particularly women and disadvantaged groups in sub-Saharan Africa, face climate-related challenges like droughts and erratic rainfall, threatening agricultural production1. Inadequate seed supply systems leave these farmers vulnerable to low productivity and pests and diseases. In Uganda, women and disadvantaged groups face several challenges related to seed systems, including limited access to quality seeds, gap in knowledge about modern agricultural practices and seed technologies, barriers in accessing markets for both purchasing seeds and selling their produce, limited access to climate-resilient seed varieties, and lack access to targeted programs and support services to address barriers to effective participation in seed systems. These challenge affects the overall agricultural productivity and food security and perpetuates poverty and limits the ability of women and disadvantaged groups to invest in improved seed technologies56. These further deepens existing gender inequalities within agri-food systems in Uganda limiting women's empowerment in agriculture78. The CGIAR's improved varieties and innovations have the potential to address the challenges, but access to quality seeds remains limited.